Revisit Decision to the Ragunan Zoological Gardens: Brand Image and Admission Price as Determination Factors - Nugroho B Sukamdani; Tatan Sukwika; Dewi A Kusumaningrum; Yohanes Sulistyadi; Fauziah Eddyono (Jurnal Mantik, 2022)
Ragunan Zoological Gardens (RZG) is one of the tourist destinations in Jakarta. To maintain its existence, RZG continues to increase the number of visitors annually. The brand image factor and the price of admission are considered by RZG managers so that tourists can revisit RZG. The study aimed to determine the effect of brand image and RZG Price of Admission on the decision to return to RZG. The research method used to survey and quantitative descriptive. The sampling technique is non-probability sampling, namely convenience or accidental sampling. The sample is that visitors have been to RZG at least once. Collecting data is done by interviewing and distributing questionnaires using a Likert scale. The analysis technique uses statistical tests, namely validity and reliability tests, variable description analysis, classical assumption tests, correlation analysis, regression analysis and hypothesis testing t test and F test. Return to RZG. Simultaneous conditions found similar results. Namely, the brand image factor and the price of admission tickets positively affect the tourist's decision to revisit RZG. The recommendations suggest managers improve RZG's prime image by enhancing services and maintaining the quality of tourism products. For example, they evaluate RZG's Brand image and prepare a corrective action plan. Suggestions for further researchers, researchers, should be able to develop research with other variables such as attractions and amenities, social media promotions, digital marketing, and others that influence visit decisions.